DYNAMICS OF NUMBER, COMPOSITION AND STRUCTURE OF THE CABARDINO-BALKARIA ORGANIZATION OF THE CPSU AS THE REFLECTION OF ALL CRISIS PROCESSES IN SOCIETY IN 1985-1991 - N. Shaozheva (Гуманитарные и юридические исследования)
The article analyzes the issues of the size, composition and structure of the Kabardino-Balkaria organization of the CPSU, reflecting the regional version of the intra-party life of the "leading and guiding force of Soviet society" in 1985-1991. The change in these key factors clearly shows how in the context of the transformation of the Soviet social and political system 1985-1991 crisis processes within the CPSU were manifested. The author's periodization, reflecting the dynamics of these processes, is substantiated. The relevance of the study is conditioned by the need to study these crisis processes within the Kabardino-Balkaria organization of the CPSU, which reflected, on the one hand, the decline of its political, ideological and organizational role in the life of the republic, degree of political adaptation to the new socio-political reality formed by the Central Committee of the Communist Party of the Soviet Union, and, on the other hand, allow to reconstruct the events of the collapse of the regional political system. The main sources of the study were archival materials collected at the Documentation Center for the Modern History of the Kabardino-Balkaria Republic, which contain detailed data on the number, age, professional, national to the Republican Party. Information obtained from archival statistics is supplemented by published personal material and media information. The work highlights the events related to the emergence of new political forces and the development of social processes, which led to a negative transformation of the role and status of the Communist Party of the Soviet Union. It shows how the emerging national social organizations, originally established as cultural centers for the revival of language, culture and history, having received some support from society, have become a real opposition force, opposing the party and Soviet bodies of the republic.